The Anti-obesity Effects of Direct Delivery of Resveratrol-encapsulated Liposomes to Inguinal White Adipose Tissue in Male APOE(*)3Leiden.CETP Transgenic Mice (P21-006-19) - Khan, Md Shahjalal Hossain (Curr Dev Nutr, 2019)
OBJECTIVES: Browning of white adipose tissue (WAT) is a promising strategy for preventing and treating obesity. Trans-resveratrol (R) has the potential to increase the energy expenditure via inducing WAT browning, but its application in obesity is limited by a low level of aqueous solubility, a high level of hepatic metabolism and toxicity. We have successfully synthesized biocompatible and biodegradable R encapsulated liposomes (Rlipo). The objective of this project is to deliver Rlipo directly to the inguinal WAT (iWAT) in mice with the goal of maximizing anti-obesity efficacy while minimizing side effects and toxicity. METHODS: Rlipo were prepared using R and soy phosphatidylcholine (soy-PC) dissolved in ethanol. After mixing and drying them under nitrogen, deionized water was added followed by sonication. Unencapsulated R was removed by ultrafiltration. The void liposomes (Vlipo) were prepared using only soy-PC. The particle size and polydispersity index (PI) of Rlipo and Vlipo were measured using a Brookhaven BI-MAS particle size analyzer. R’s encapsulation efficiency and solubility were measured using a liquid chromatography-mass spectrometry. Male APOE(*)3Leiden.CETP mice having human-like lipoprotein metabolism were fed with a high-fat diet (45% of calorie from fat) for 10 weeks. After treating the high-fat diet for 4 weeks, mice received iWAT injection of Rlipo, Vlipo, free R and saline (control) once a week. R concentration was 17.5 mg/kg body weight/week. Body weight and food intake were measured weekly. Body composition of mice was measured using an EchoMRI(TM) every other week. Core body temperatures of mice were determined using a Type T thermometer. Glucose tolerance test (GTT) was performed at the 4(th) week of treatment. RESULTS: Rlipo increased the aqueous solubility of R by more than 100 times. The size of Rlipo and Vlipo was 170 ± 6 nm and 140 ± 7 nm, respectively. Their PI values were less than 0.2. The encapsulation efficiency of Rlipo was 99.8%. The post-treatment core body temperatures for control, free R, Vlipo and Rlipo groups were 36.2°C, 36.2°C, 36.6°C, and 37.0°C, respectively. Food intake was similar among 4 groups. Compared to other groups, the Rlipo-treated mice had the lowest body weight, body fat mass, and body fat percentage. The Rlipo group had the lowest area under the curve in the GTT among 4 groups. CONCLUSIONS: Nanoencapsulation increased R’s solubility and enhanced its anti-obesity efficacy. FUNDING SOURCES: NIH/NCCIH (Grant R15AT008733).